Simulating the Impact of a Cigarette Minimum Floor Price Law on Adult Smoking Prevalence in California. Issue 10 (9th March 2020) - Golden, Shelley D; Kim, KyungSu; Kong, Amanda Y; Tao, Vivian Qingzi; Carr, Derek; Musburger, Pratima
Abstract: Introduction: Minimum floor price laws (MFPLs) are an emerging tobacco control policy that sets a minimum price below which a specific tobacco product cannot be sold. MFPLs target cheaper products and may disproportionately impact consumers choosing low price brands or using discounts to reduce prices. We developed a static microsimulation model for California, United States to project short-term effects of different MFPL options for a 20-stick pack of cigarettes on adult smoking behaviors. Aims and Methods: We simulated 300 000 individuals defined by race and ethnicity, sex, age, and poverty status. Smoking behaviors and cigarette prices were assigned based on demographic distributions in the 2014–2016 California Behavioral Risk Factor Surveillance System. We drew 100 random samples ( n = 30 000), weighted to state-level California demographic characteristics. We simulated six MFPL options and modeled impacts on smoking prevalence and cigarette consumption, in general, and separately for those in households below or above 250% of the federal poverty level, assuming a price elasticity of −0.4. Results: Predicted changes in prices, prevalence, and consumption increased exponentially as the floor price increased from $7.00 to $9.50. Assuming 15% policy avoidance, projected increases in average cigarette prices ranged from $0.19 to $1.61. Decreases in smoking prevalence ranged from 0.05 to 0.43 percentage points, and decreases in average monthly cigarette consumption ranged from 1.4 to 12.3 cigarettes. Projected prices increased, and prevalence and consumption decreased, more among individuals in households below 250% federal poverty level. Conclusions: MFPLs are a promising tobacco control strategy with the potential to reduce socioeconomic disparities in cigarette smoking prevalence and consumption. Implications: Despite reductions in adult smoking prevalence, significant socioeconomic disparities remain, with lower-income groups smoking at substantially higher levels than higher-income groups. Policies that set a floor price below which a tobacco product cannot be sold could reduce socioeconomic disparities in smoking, depending on variation in prices paid by smokers prepolicy. By using a microsimulation model to predict changes in smoking for different population groups in California under several floor price scenarios, this study demonstrates that MFPLs have the potential to reduce adult smoking prevalence overall, and especially for lower-income tobacco users.